(Un)expected Monetary Policy Shocks and Term Premia - Martin Kliem; Alexander Meyer-Gohde (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2017)
We analyze an estimated stochastic general equilibrium model that replicates key macroeconomic and fi nancial stylized facts during the Great Moderation of 1983-2007. Our model predicts a sizeable and volatile nominal term premium - comparable to recent reduced-form empirical estimates - with real risk two times more important than inflation risk for the average nominal term premia. The model enables us to address salient questions about the effects of monetary policy on the term structure of interest rates. We fi nd that monetary policy shocks can have differing effects on risk premia. Actions by the monetary authority with a persistent effect on households' expectations have substantial effects on nominal and real risk premia. Our model rationalizes many of the opposing findings on the effects of monetary policy on term premia in the empirical literature.
Keywords: E13; E31; E43; E44; E52; 330; DSGE model; Bayesian estimation; Term structure; Monetary policy